Water Level Monitoring and Controlling Using Bluetooth in Agriculture (International Journal of Engineering and Computer Science, 2017)
The application of wireless sensor network (WSN) for a water quality monitoring is composed of a number of sensor nodes with a networking capability that can be deployed for detecting the water level in land. In this project, we use some sensors for detecting the water level from testing the soil, and report the details to famers mobile phone via wirelessly. The farmer mobile phone related to electricity water pump and sensor device, the electricity water pump is controlled by the farmer on wireless network. The Water level was calculated in digitally and it was displayed on mobile application in the farmer’s smart phones. And we can control the electric water pump to set ON/OFF by the mobile app. This paper proposes how such monitoring system can be setup emphasizing on the aspects of low cost, easy ad hoc installation and easy handling and maintenance. In this paper, the fundamental design and implementation of WSN featuring a high-power transmission Bluetooth based technology together with the IEEE 802.15.1 compatible transceiver is proposed. The developed platform is cost-effective and allows easy customization